Effectiveness of a 2-dose varicella vaccination program in Changzhou, China, during the transitional period (2017–2022): a registry-based case-cohort study - Suting Xiong; Changlei Han; Dan Wu; Xiaomeng Mi; Peipei Zhang; Han Gao; Gan Cao; Fang Yao; Cong Chen; Xufeng Lv (BMC Public Health)
Abstract Background The benefits of improving coverage and timeliness of varicella vaccination need to be quantified in countries where varicella vaccine (VarV) has not yet been included in national immunization programs. This longitudinal study analyzed the vaccine effectiveness (VE) of the varicella vaccination program implemented in Changzhou City during the transitional period (2017–2022). Methods Using the Immunization Information System and National Notifiable Infectious Disease Surveillance System registry data, this retrospective case-cohort study assessed the VEs of varicella vaccination for Changzhou children born from 2016 to 2021. The subcohort was sampled using inverse probability weighting for the survival analysis design to evaluate the VEs under different dosages and cost types, eliminating confounding by age and location area. Sensitivity analysis for the exclusion part assessed the study's robustness. Results A total of 5,172 children (1.12%) were sampled to the subcohort for studies, including 2,299 cases. VEs significantly rose with each successive dose, reaching 82.54% and 97.91%. VEs were lower for the single-dose subgroups until 2020, with significant increases in VEs in all subgroups in 2020 and after that. Most children who did not benefit from the “1–4” Vaccination Program had lower VEs due to delayed vaccination. Conclusion Improving 2-dose VarV vaccine coverage and timely vaccination could enhance the immune barrier for susceptible children. During the transitional period, the “1–4” Vaccination Program of VarV positively impacted coverage and timeliness in Changzhou.